The nocturnal bottleneck and the evolution of activity patterns in mammals. - Gerkema, M; Davies, W; Foster, R; Menaker, M; Hut, R (2013)
In 1942, Walls described the concept of a 'nocturnal bottleneck' in placental mammals, where these species could survive only by avoiding daytime activity during times in which dinosaurs were the dominant taxon. Walls based this concept of a longer episode of nocturnality in early eutherian mammals by comparing the visual systems of reptiles, birds and all three extant taxa of the mammalian lineage, namely the monotremes, marsupials (now included in the metatherians) and placentals (included in the eutherians). This review describes the status of what has become known as the nocturnal bottleneck hypothesis, giving an overview of the chronobiological patterns of activity. We review the ecological plausibility that the activity patterns of (early) eutherian mammals were restricted to the night, based on arguments relating to endothermia, energy balance, foraging and predation, taking into account recent palaeontological information. We also assess genes, relating to light detection (visual and non-visual systems) and the photolyase DNA protection system that were lost in the eutherian mammalian lineage. Our conclusion presently is that arguments in favour of the nocturnal bottleneck hypothesis in eutherians prevail.